2009
DOI: 10.1093/jpepsy/jsp069
|View full text |Cite
|
Sign up to set email alerts
|

A Review of HIV Prevention Interventions for Juvenile Offenders

Abstract: Several HIV prevention programs with juvenile offenders have led to sexual risk reduction, although effect sizes are modest. Most existing programs have neglected to address the impact of family, mental health, and substance use on HIV risk. More work is needed to develop evidence-based interventions that include HIV prevention strategies relevant and appropriate for the juvenile justice setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
51
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(55 citation statements)
references
References 37 publications
2
51
2
Order By: Relevance
“…Nevertheless, youth behavioral change in the family-based intervention might represent a regression to the mean effect for risky sex acts and marijuana use and as such, a larger trial is needed for replication of these findings. Despite significant group differences on key primary behavioral outcomes, effect sizes were small, but not too distant from prior HIV prevention trial findings with juvenile offenders (Tolou-Shams et al, 2010). Structural or systems-level interventions may be more effective in achieving greater behavioral change for youth on a broader scale.…”
Section: Discussioncontrasting
confidence: 69%
See 3 more Smart Citations
“…Nevertheless, youth behavioral change in the family-based intervention might represent a regression to the mean effect for risky sex acts and marijuana use and as such, a larger trial is needed for replication of these findings. Despite significant group differences on key primary behavioral outcomes, effect sizes were small, but not too distant from prior HIV prevention trial findings with juvenile offenders (Tolou-Shams et al, 2010). Structural or systems-level interventions may be more effective in achieving greater behavioral change for youth on a broader scale.…”
Section: Discussioncontrasting
confidence: 69%
“…These data provide a compelling case to specifically target substance use within HIV prevention interventions for juvenile offenders. Underlying constructs contributing to and/or exacerbating psychiatric distress, substance use and sexual risk behavior among these youth, such as extensive trauma exposure (Evans-Chase, 2014), greater emotion dysregulation (Lescano, Brown, Miller, & Puster, 2007) and family dysfunction are also important to consider when developing and testing HIV prevention interventions for substance using offenders (Tolou-Shams, Stewart, Fasciano, & Brown, 2010). We briefly review the evidence for these associations and the rationale for targeting these areas in a comprehensive family-based HIV prevention program for juvenile offenders.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A meta-analysis of HIV prevention programs for juvenile offenders showed that most existing programs have not addressed the critical impact of family, mental health, and substance use on HIV risk. 54 In summary, the identification of incarcerated girls' health and mental health needs, including the relationship between their drug use and sexual behaviors, illustrates the urgent need for tailored interventions and pre-release coordination of services for young female offenders. These activities are imperative in order to disrupt the cycle to high-risk behaviors and recidivism among incarcerated female adolescents in the United States.…”
Section: Implications For Public Health Programmingmentioning
confidence: 99%